Determination of the bruise indexes of oil palm fruits - Suryanto, Hadi; Ahmad, Desa; Akande, Fatai Bukola (Elsevier, 2009)

(untitled)
This study determines the bruise indexes of oil palm fruits as criteria for use in the design of the oil palm fruits stripper. Bruise has been classified into four according to the bruise area and the effect of each category on the free fatty acid (FFA) has been investigated. The FFA developed by each category of the bruise was determined at different delay period of 4 and 12 h between stripping and oil extraction. Statistical analysis showed that there was no significant relationship at 1% significant level between delay period and the FFA. Regression analysis was also carried out on the FFA of different ripeness levels and the bruise index and a regression model was developed relating the amount of FFA at different levels of ripeness and bruise index. At all levels of ripeness, the percentage of free fatty acid developed by bruised fruits increased with increasing bruise index.